Biocompatible mechano-bactericidal nanopatterned surfaces with salt-responsive bacterial release. (15th March 2022) - Liu, Ziting; Yi, Yaozhen; Song, Lingjie; Chen, Yuxiang; Tian, Limei; Zhao, Jie; Ren, Luquan
Abstract: Bio-inspired nanostructures have demonstrated highly efficient mechano-bactericidal performances with no risk of bacterial resistance; however, they are prone to become contaminated with the killed bacterial debris. Herein, a biocompatible mechano-bactericidal nanopatterned surface with salt-responsive bacterial releasing behavior is developed by grafting salt-responsive polyzwitterionic (polyDVBAPS) brushes on a bio-inspired nanopattern surface. Benefiting from the salt-triggered configuration change of the grafted polymer brushes, this dual-functional surface shows high mechano-bactericidal efficiency in water (low ionic strength condition), while the dead bacterial residuals can be easily lifted by the extended polymer chains and removed from the surface in 1 M NaCl solution (high ionic strength conditions). Notably, this functionalized nanopatterned surface shows selective biocidal activity between bacterial cells sand eukaryotic cells. The biocompatibility with red blood cells (RBCs) and mammalian cells was tested in vitro. The histocompatibility and prevention of perioperative contamination activity were verified by in vivo evaluation in a rat subcutaneous implant model. This nanopatterned surface with bacterial killing and releasing activities may open new avenues for designing bio-inspired mechano-bactericidal platforms with long-term efficacy, thus presenting a facile alternative in combating perioperative-related bacterial infection. Statement of significance: Bioinspired nanostructured surfaces with noticeable mechano-bactericidal activity showed great potential in moderating drug-resistance. However, the nanopatterned surfaces are prone to be contaminated by the killed bacterial debris and compromised the bactericidal performance. In this study, we provide a dual-functional antibacterial conception with both mechano-bactericidal and bacterial releasing performances not requiring external chemical bactericidal agents. Additionally, this functionalized antibacterial surface also shows selective biocidal activity between bacteria and eukaryotic cells, and the excellent biocompatibility was tested in vitro and in vivo. The new concept for the functionalized mechano-bactericidal surface here illustrated presents a facile antibiotic-free alternative in combating perioperative related bacterial infection in practical application. Graphical abstract: Image, graphical abstract